(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2021)
Electromagnetic phenomena is based on electric charge and spin. However, Maxwell equations are just macroscopic. There is a microscopic EM phenomena to be understood. A performance originated from electric charge microscopic behavior. Thus, keeping on mind the two basic EM postulates, which are light invariance and charge conservation, Maxwell is extended to a Four Bosons Electromagnetism. It says that, the macroscopic Maxwell equations does not describe all electromagnetism. The electric charge physics has been studied microscopically through elementary particle physics. A new perception of EM phenomena emerges based on three interconnected charges +, 0, − under four intermediated bosons Aµ, Uµ, V±µ . From Maxwell photon, EM becomes a systemic cooperation between four fields. This quadruplet originates a new electric charge physics. New features for electric charge conservation, exchange, conduction, interaction are derived. The research is to analyze the Four Bosons Electromagnetism gauge invariance and EM flux. The model is studied under U(1), SO(2)global and U(1)×SO(2)global symmetries. Two approaches are considered. Based on fields strengths and on fields. A gauge invariant quadruplet physics is obtained under free coefficients conditions. A nonlinear EM flux appears. Without requiring electric charge as source nonlinear fields work as own sources for flowing spin-1 and spin-0 waves and particles. It flows through a four potential field quadruplet, granular and collective fields strengths. A self contained EM is constituted providing a nonlinear physicality that precedes physical constants as electric charge and medium parameters. The EM meaning is enlarged and we have to understand on the physical structures generated by this antireductionist nonlinear four bosons microscopic electromagnetism. Determine the corresponding fields blocks which are real and gauge invariants. They are identified as the electromagnetic domains. The Four Bosons EM develops interdependent EM domains. Interlaced physical sectors sharing a common EM energy context. Lagrangian, equations of motion, conservation laws are expressing such domains physics. They correspond to physical sectors where each one contains its own EM energy.